Association Between Smoking and Central Obesity in Individuals Aged ≥40 Years Based on the Indonesian Family Life Survey-5 - Hendri, Gabriel Anetta; Kurniawan, Felicia; Astiarani, Yunisa; Santi, Bryany Titi; Kristian, Kevin (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Obesity and smoking are major public health concerns and leading causes of preventable morbidity and mortality. Smoking may contribute to central obesity through multiple mechanisms, and individuals aged ≥40 years are at higher risk. This study aimed to examine the association between smoking and central obesity, considering sociodemographic factors, using data from the Indonesian Family Life Survey-5 (IFLS-5).Methods: A cross-sectional study was conducted using secondary data from IFLS-5. Participants included Indonesians aged ≥40 years with complete data on smoking and waist circumference. Smoking status was assessed using the Brinkman Index (BI) and classified as light (0–199), moderate (200–599), or heavy (>600). Central obesity was defined as waist circumference ≥90 cm for male and ≥80 cm for female. Associations were analyzed using Chi-square tests at 95% confidence interval.Results: Of 3,391 participants, the majority were male (95.4%) with a mean age of 52.76±9.78 years (range 40–101). The prevalence of central obesity was 22.3% (n=790), and the largest group of participants were moderate smokers (54.9%). Central obesity was significantly associated with smoking status (p=0.003), age (p<0.001), gender (p<0.001), and education level (p<0.001). No significant associations were found with marital status (p=0.826), occupation (p=0.374), or residence (p=0.750).Conclusions: Smoking, age, gender, and education level are significantly associated with central obesity among Indonesians aged ≥40 years. Preventive measures, including smoking cessation and lifestyle interventions, are essential to reduce central obesity and the risk of cardiovascular disease.